Nivel de conocimiento del personal de enfermería sobre los accidentes biológicos en la unidad de cuidados intensivos - Bravo Robles, María Isabel (2025)
Background: Nursing staff in Intensive Care Units (ICUs) face a high risk of exposure to infectious biological agents due to direct contact with body fluids and medical equipment. This can lead to transmission of serious diseases such as HIV and hepatitis B and C, especially when there is lack of training and inconsistent use of personal protective equipment (PPE). Introduction: This study focuses on assessing knowledge of nurse about biological accidents in the ICU, highlighting the importance of biosafety in infection prevention. Objective: To assess the level of knowledge of nursing staff about biological accidents in the ICU, identify gaps in training and propose strategies to improve training and the implementation of biosafety protocols. Methods: A quantitative and descriptive study was conducted by surveying 24 nurses in an ICU. Results were analyzed, using frequencies and percentages to assess knowledge and preventive practices. Results: 78% of respondents received prevention training, but 46% have experienced biological accidents, mainly needle sticks. Although 82% have a general understanding of biosafety procedures, only 9% claim to be aware of them. Conclusions: A deficiency was found in continuous training and use of PPE. Finally, it is recommended to implement regular training programmes and simulations to improve adherence to biosafety protocols, which can significantly reduce risks for nurses and patients